Investigative study on dimensional accuracy of machined cavity formed during EDM of AISI 1035. (2021) - Prakash, Jai; Equbal, Md. Israr; Equbal, Azhar
Abstract: Effect of machining parameters on dimensional accuracy of machined cavity is investigated for EDM (electrical discharge machining) of AISI 1035 steel. Machining accuracy is measured in terms of depth ( H ) of machined cavity obtained during machining with respect to original depth of 4 mm given for machining. A total of 20 experiments were performed in accordance with response surface methodology (RSM). Working current ( I ), spark on time ( Ton ) and spark off time ( Toff ) are taken as machining variables. Significant machining factors were determined using ANOVA (Analysis of variance) and the generated model is validated using normality test. Surface plots are used to explain the deviations in machining depth when machining parameters are continually varied. Genetic algorithm (GA) approach is used as an optimization technique to determine the optimum machining factors to minimize the deviation in machining depth ( ΔH ).